2004
DOI: 10.1007/s11141-005-0039-0
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric losses in CVD diamonds in the millimeter-wave range at temperatures 300?900 K

Abstract: UDC 538.955+538.956We study losses in different CVD diamonds in the frequency range 50-210 GHz at temperatures 300-900 K by using a high-Q open Fabry-Perot cavity. It is found that the effective activation energies determining a sharp increase in losses at high temperatures are distributed in the range 0.4-0.8 eV. We propose a formula which relates the frequency and temperature dependences of losses for different CVD-diamond specimens in the first approximation. Suggestions on the nature of these losses are pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Our previous study [12][13][14] have confirmed that the diamond sample with a more perfect inner structure, having the minimum number of relatively large-size microcaverns, has absorption closer to the theoretical curve up to 350 GHz. However, the studies of this sample in the 350-520 GHz range [6] clearly revealed the influence of the absorption scattering mechanism (Fig.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Our previous study [12][13][14] have confirmed that the diamond sample with a more perfect inner structure, having the minimum number of relatively large-size microcaverns, has absorption closer to the theoretical curve up to 350 GHz. However, the studies of this sample in the 350-520 GHz range [6] clearly revealed the influence of the absorption scattering mechanism (Fig.…”
Section: Resultssupporting
confidence: 58%
“…The resonator spectrometer earlier developed at the IAP RAS, methods of measurement, and the results of studying various materials from 40 GHz up to 370 GHz are well described in [2][3][4][5][6]12]. So in present paper, a detailed description of the resonator excitation system and the frequency phase lock system, which were essentially modified for operation at the 350-520 GHz, is presented.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, it is not necessary to measure the idle-resonator Qfactor, i.e., it is not necessary to extract the studied sample from the resonator. It is fairly convenient to study temperature dependences of tan δ by placing the studied sample in heating or cooling fitting inside the resonator [6].…”
Section: Measuring the Dielectric Parametersmentioning
confidence: 99%
“…This paper aims at determining the absorption properties of such materials in the millimeterwave range at temperatures up to the temperature of composition sintering, which exceeds 1000 • C. At such high temperatures, it is rather difficult to use the conventional waveguide methods of measuring dielectric properties of the materials. The use of the methods based on application of millimeter-wave beams also meets great technical difficulties caused by the necessity of using high-temperature heating devices [4][5][6]. In addition, the absorption of millimeter waves in metal-ceramic composite materials is, as a rule, great.…”
Section: Introductionmentioning
confidence: 99%